Self-learning modules in technical report writing for engineering technology students, parts I and II - Resabal, Ester Sarmiento 1951- (1975)
These self-instructional modules have been prepared to meet the need for instructional materials in Technical Report Writing, a writing course designed for the three-year engineering technology curriculum. These have also been prepared in response to the new Philippine Bilingual policy which assigns the English language within the domain of science and technology and in recognition of the primacy of an individualized approach in learning.
Thesis (M.A.T.)--University of the Philippines
Keywords: Technical writing